Delivery of BR2‐SOX17 fusion protein can inhibit cell survival, proliferation, and invasion in gastric cancer cells through regulating Klotho gene expression. (1st July 2020) - Yang, Lixia; Wu, Yue; He, Heli; Hu, Fan; Li, Mei; Mo, Li; Xiao, You; Wang, Xiaoyan; Xie, Biao
Abstract: The prognosis of advanced gastric cancer is poor and understanding the biology and subsequent development of new targeting therapy is still an urgent need. This study was conducted to explore the effect of BR2 (a 17‐amino acid peptide)‐SOX17 (human sex determining region Y (SRY)‐related high‐mobility group (HMG) box protein family member 17) fusion protein on Klotho gene expression in gastric cancer cells. The regulatory effects of SOX17 on Klotho gene in gastric cancer cells were tested using dual‐luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay. The therapeutic effects of BR2‐SOX17 were evaluated by proliferation, colony formation, invasion assay, and cell apoptosis analysis. Results showed that SOX17 enhanced Klotho gene expression in gastric adenocarcinoma cells through binding to the promoter of Klotho gene. BR2‐SOX17 fusion protein was effective in delivering SOX17 into gastric cancer cells and subsequently inhibited the cell proliferation, colony formation, and invasion, increased E‐cadherin protein expression, decreased vimentin protein expression, as well as induced apoptosis. Our findings suggested SOX17 can bind to the promoter of Klotho gene to enhance Klotho gene expression in gastric cancer cells. The fused BR2‐SOX17 protein is an effective agent for targeting therapy of gastric cancer.